2005
DOI: 10.1177/0145445503261172
|View full text |Cite
|
Sign up to set email alerts
|

Financial Management and Job Social Skills Training Components in a Summer Business Institute

Abstract: Ninety-two adolescents, predominantly ethnic minority high school students, participated in a structured Summer Business Institute (SBI). Participating youth were randomly assigned to receive either job social skills or financial management skills training components. Students who additionally received the job social skills training component were more likely to recommend their employment agency to others than were youth who received the financial management component, rated their overall on-the-job work exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In all three of the structured situations (Facing a job interview, Offering a colleague some help and Dealing with a superior's fair criticism) the identification of important gains were identified in both groups' participants, as well as maintaining this spirit of leaning throughout the last evaluations. The acquirement of skills for job interviews and other professional experiences are in accordance with the findings of A. Del Prette and Del Prette (2003), Donohue et al (2005) and Sarriera, Câmara and Berlim (2000), which also proved the importance of developing social skills in preparation for the labor environment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In all three of the structured situations (Facing a job interview, Offering a colleague some help and Dealing with a superior's fair criticism) the identification of important gains were identified in both groups' participants, as well as maintaining this spirit of leaning throughout the last evaluations. The acquirement of skills for job interviews and other professional experiences are in accordance with the findings of A. Del Prette and Del Prette (2003), Donohue et al (2005) and Sarriera, Câmara and Berlim (2000), which also proved the importance of developing social skills in preparation for the labor environment.…”
Section: Discussionsupporting
confidence: 86%
“…P. Del Prette & Del Prette, 2005;Gresham, 2009). These results show that the training of social skills for the work environment is able to provide advantages in referring individuals to recruitment agencies, exceeding in performance in the face of job interviews and having confidence to seek employment, which is also supported by the findings from other studies Donohue et al, 2005;Sarriera et al, 2000).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Along this vein, the results of this study suggest it is important to develop vocational interventions in this population that are focused on job satisfaction. For mothers who are employed and assessed to evidence low employment satisfaction, interventions might focus on modifying employment related attitudes to assist positive perspective and teaching new behaviors that can assist these mothers in deriving more satisfaction from their jobs (de Graaf-Zijl, 2012; Donohue et al, 2005; Peng & Mao, 2014). Alternatively, it makes sense to assist the employees of these mothers to incorporate programs that are designed to enhance their satisfaction in the workplace environment.…”
Section: Discussionmentioning
confidence: 99%
“…Social skills can act as a protection factor for professional placement because they help people with physical disabilities deal with the demands of assertiveness (e.g., those related to the defense of their rights to accessibility and adaptation of workplaces) and expand friendships and social support links, which may increase opportunities for interaction and exposure to different professional contexts and activities (Murta & Guimarães, 2007;Wilson et al, 2006). Work-related SSPs have previously been tested with young people with and without disabilities and have shown that learning social skills contributes to more satisfactory performance in job interviews and in the activities of the role, especially in measures that have assessed initiative and the ability to interact with others in the workplace (Campos & Almeida, 2010;Donohue et al, 2005;Lindsay et al, 2012;Lopes, Gerolamo, Del Prette, Musetti, & Del Prette, 2015;Phillips et al, 2014;Soresi & Nota, 2000).…”
Section: Introductionmentioning
confidence: 99%